2002
DOI: 10.1002/mds.1246
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Annonaceae for dopaminergic neurons: Potential role in atypical parkinsonism in Guadeloupe

Abstract: In the French West Indies there is an abnormally high frequency of levodopa-resistant parkinsonism, suggested to be caused by consumption of fruit and infusions of tropical plants, especially Annona muricata (corossol, soursop). To determine whether toxic substances from this plant can cause the neuronal degeneration or dysfunction underlying the syndrome, we exposed mesencephalic dopaminergic neurons in culture to the total extract (totum) of alkaloids from Annona muricata root bark and to two of the most abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 24 publications
1
56
0
1
Order By: Relevance
“…Another study demonstrated that graviola induced growth inhibition of human breast cancer cells in vitro and in vivo through a mechanism involving the EGFR/ERK signaling pathway [16]. In terms of toxicity, graviola may cause movement disorders and myeloneuropathy with symptoms mimicking Parkinson's disease [17]. Our patient did not suffer any significant side effects.…”
Section: Discussionmentioning
confidence: 53%
“…Another study demonstrated that graviola induced growth inhibition of human breast cancer cells in vitro and in vivo through a mechanism involving the EGFR/ERK signaling pathway [16]. In terms of toxicity, graviola may cause movement disorders and myeloneuropathy with symptoms mimicking Parkinson's disease [17]. Our patient did not suffer any significant side effects.…”
Section: Discussionmentioning
confidence: 53%
“…TH ϩ cells represent only a small percentage of the neurons in mesencephalic cultures (Michel et al, 1999). To determine whether PX also affected the survival of non-DA neurons, which are predominantly GABAergic (Lannuzel et al, 2002), we labeled the entire population of neuronal cells with an antibody against MAP-2. Different from what we observed with DA neurons, the number of MAP-2 ϩ neuronal cells remained stable during the maturation process of mesencephalic cultures (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The two most abundant alkaloids in this plant, the benzyl-tetra-hydroisoquinoline reticuline and the tetrahydroprotoberberine coreximine were toxic to DA neurons 20 ( Table 2). The concentrations of the alkaloids causing DA cell death were, however, relatively high (ranging from 13 to 300 lM) and thus not likely to be reached in the brains of patients.…”
Section: The Complex I Inhibitor Annonacin As a Possible Etiological mentioning
confidence: 99%